DETERMINAN PERILAKU SEKSUAL BERISIKO TERTULAR HIV/AIDS DAN INFEKSI MENULAR SEKSUAL (IMS) PADA PEKERJA PERUSAHAAN DI TANJUNG JABUNG BARAT PROVINSI JAMBI - Puspita Sari; Solihin Sayuti; Pahrur Razi (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: HIV or Human Immunodeficiency Virus is a type of virus that attacks the immune system and slowly weakens a person's ability to fight other diseases by destroying important cells that function to control and support the human immune system, Tanjung Jabung Barat Regency has many companies and company workers have a high workload as a result, workers have a risk of contracting HIV / AIDS and STIs, 39 cases of HIV / AIDS cases and 32 STI cases. Method: This type of research is quantitative with a cross sectional study design. Sample 102 people. Sampling by incidental sampling. Data analysis was univariate, bivariate with Chi square and multivariate with logistic regression. Results: The results showed that there was a relationship between marital status, knowledge, perceptions of vulnerability, perceived seriousness, perceived barriers, perceptions of self-efficacy and sexual behavior at risk of contracting HIV / AIDS and STIs. The factor that has a strong influence on risky sexual behavior is the perception of inhibition with the Odds Ratio (OR = 2.416. 95% CI 1.195–4.882). Conclusion: The need for health promotion of workers regarding HIV / AIDS and STIs through various media to increase knowledge of workers and companies are expected to support the provision of communication, information and education (IEC) to company workers, through facilitating and providing access to company workers to obtain information. about HIV / AIDS and STIs such as holding outreach on HIV / AIDS and STIs, posting information posters about HIV / AIDS and STIs and etc.